2006
DOI: 10.1002/cjoc.200690197
|View full text |Cite
|
Sign up to set email alerts
|

Design of Multivalent Galactoside Ligands and Their Binding to Hepatic Asialoglycoprotein Receptor

Abstract: In an effort to find highly efficient ligands for hepatic asialoglycoprotein receptor (ASGPR), four cluster galactosides with different scaffolds were synthesized in this paper. The affinity of these compounds for ASGPR was analyzed by binding study in vitro. The results showed that trivalent cluster galactosides behaved better than divalent analogues and the cluster galactosides with aryl groups on their scaffolds presented better binding affinity than those with aliphatic chain scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The inhibition by one GalNAc unit in the polymer was comparable to ASF and much greater than free GalNAc when compared with the GalNAc equivalent concentration of PMAGalNAc 62 chains. These data suggest that multivalent binding imparts higher receptor affinity, in accordance with previous findings on the effect of ligand valency on binding affinity to ASGPRs. ,,, Previous studies have used ligand-functionalized, radiolabeled proteins at 4 °C for measuring IC 50 values to show that biantennary and triantennary structures can have 3–4 orders of magnitude higher binding constants compared to monovalent structures. , Uptake studies of fluorescently labeled compounds at 37 °C (similar to our current study) have also shown a similar trend , with biantennary and triantennary ligands, even though the IC 50 values differ between these two approaches due to differences in experimental design. These data suggest that a serial arrangement of GalNAc in a block of 62 repeat units also provides high binding affinity due to the cluster glycoside effect (yielding 5 orders of magnitude higher affinity than free GalNAc) .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The inhibition by one GalNAc unit in the polymer was comparable to ASF and much greater than free GalNAc when compared with the GalNAc equivalent concentration of PMAGalNAc 62 chains. These data suggest that multivalent binding imparts higher receptor affinity, in accordance with previous findings on the effect of ligand valency on binding affinity to ASGPRs. ,,, Previous studies have used ligand-functionalized, radiolabeled proteins at 4 °C for measuring IC 50 values to show that biantennary and triantennary structures can have 3–4 orders of magnitude higher binding constants compared to monovalent structures. , Uptake studies of fluorescently labeled compounds at 37 °C (similar to our current study) have also shown a similar trend , with biantennary and triantennary ligands, even though the IC 50 values differ between these two approaches due to differences in experimental design. These data suggest that a serial arrangement of GalNAc in a block of 62 repeat units also provides high binding affinity due to the cluster glycoside effect (yielding 5 orders of magnitude higher affinity than free GalNAc) .…”
Section: Resultssupporting
confidence: 92%
“…These data suggest that multivalent binding imparts higher receptor affinity, in accordance with previous findings on the effect of ligand valency on binding affinity to ASGPRs. 50,51,65,66 Previous studies have used ligand-functionalized, radiolabeled proteins at 4 °C for measuring IC 50 values to show that biantennary and triantennary structures can have 3−4 orders of magnitude higher binding constants compared to monovalent structures. 50,54 Uptake studies of fluorescently labeled compounds at 37 °C (similar to our current study) have also shown a similar trend 51,66 with biantennary and triantennary ligands, even though the IC 50 values differ between these two approaches due to differences in experimental design.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…To compare the self-assembly behavior of Bz - and Ac -protected glycopolymers, the corresponding monomers were designed first. As shown in Scheme , glycosylation donors Bz-1 and Ac-1 were prepared via three steps according the reaction conditions reported in the literature . After glycosylation reaction with the same acceptor S1 , the vinyl group was successfully coupled to Bz-1 and Ac-1 , generating new monomers Bz-2 and Ac-2 .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, some of these are moisture sensitive and thermally not very stable. To the best of our knowledge the derivatives of 4-(trans-4-n-alkylcyclohexyl)benzene is found to be more advantageous than benzoic acid phenyl esters, biphenyl derivatives, Schiff's base derivatives, etc, based on viscosity, temperature range of the mesophase and other physical properties [18][19][20]. Very recently, Tamaoki et al [21] and Wu [22,23] synthesized a series of novel dimer compounds containing cholesteryl and phenyl benzoate groups or azobenzene dimer in which the two mesogenic units were linked through dicarboxylic ester bonds.…”
Section: Introductionmentioning
confidence: 99%